1994
DOI: 10.1007/bf00685925
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the human and murine multidrug-resistance phenotype with megestrol acetate

Abstract: MA is an orally active PG derivative with an excellent safety profile that is used primarily for the treatment of carcinomas of the breast and endometrium. We investigated the potential application of MA as an MDR-reversal agent using cell culture and human tumor xenograft models. The reversing activity of MA in vitro was compared with that of PG and VER in two human MDR cell lines, the colon carcinoma HCT-116/VM46 and the breast carcinoma MCF-7/ADR, and in a murine cell line, J774.2. At concentrations as low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…P-gp expression is associated with resistance to a number of natural and semisynthetic cytotoxic drugs in vitro including the anthracyclines, mitomycin C, vinca alkaloids, epipodophyllotoxins and actinomycin D (Chin et al, 1993). P-gp-mediated drug resistance can be modulated by a number of chemically dissimilar drugs, including verapamil, quinine, quinidine, cyclosporin A and hydrophobic steroids, such as progesterone or megestrol acetate (MA) (Wang et al, 1991;Fleming et al, 1992;Bellamy and Dalton, 1994), thereby decreasing drug resistance. Clinically, there are practical difficulties in the routine clinical use of the majority of these drugs because of significant toxicities.…”
mentioning
confidence: 99%
“…P-gp expression is associated with resistance to a number of natural and semisynthetic cytotoxic drugs in vitro including the anthracyclines, mitomycin C, vinca alkaloids, epipodophyllotoxins and actinomycin D (Chin et al, 1993). P-gp-mediated drug resistance can be modulated by a number of chemically dissimilar drugs, including verapamil, quinine, quinidine, cyclosporin A and hydrophobic steroids, such as progesterone or megestrol acetate (MA) (Wang et al, 1991;Fleming et al, 1992;Bellamy and Dalton, 1994), thereby decreasing drug resistance. Clinically, there are practical difficulties in the routine clinical use of the majority of these drugs because of significant toxicities.…”
mentioning
confidence: 99%
“…MG is a strong reversal agent: its capacity to increase intracellular accumulation of vincristine is 2-3-fold that of progesterone [6]. Previous results have shown that a daily dose of 800 mg MG resulted in a plasma concentration of 2 ÎŒM [21]; however, to reverse MDR, 5 ÎŒM is necessary in theory. Because high doses of MG induce vomiting, oedema, dizziness and androgen-like side-effects, the ideal effective concentration is difficult to obtain in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The reversal mechanism consists of, for example, binding directly to P-gp, inhibiting the transport function of drug efflux, increasing the intracellular accumulation of the drug and changing lipid mobility in the plasma membrane [4, 10, 11, 12]. However, different compounds have different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…94,98,[121][122][123][124][125][126][127][128][129][130] Paired human cell lines used as xenografts are described in the Tables 7 and 8. [131][132][133][134][135][136][137][138][139][140][141][142][143][144] In the ideal situation, modulators of MDR do not enhance cytotoxicity in parental tumors, while enhanced antitumor effects can be observed in MDR tumors. It should be noted that even in the most often used tumor model, the P388 leukemia, this is not the case, because the parental P388 cell line expresses low levels of P-glycoprotein and is sensitive to reversal activity.…”
Section: A Spontaneous and Induced Mdr Tumorsmentioning
confidence: 99%